Сравнительный анализ схем включения обмоток линейного импульсного электродвигателя - Милых, В.И.; Ткаченко, С.В. (Електротехніка і електромеханіка, 2011)
Variants of reactor and armature windings connection diagrams for a linear electric motor of percussion action on ground under exploration are considered. The connection diagrams are compared by means of the motor pulsed operation computation on the basis of formulated mathematical models. Their feature is nonlinear two- and three-parameter functions of the windings differential inductive parameters and electromagnetic force of the reactor and the armature interaction.